Knowledge, Attitude and Practices Regarding Cervical Cancer and Human Papilloma Virus (HPV) Vaccination - Meeshal Khan; Amara Zafar; Ramsha Muneer; Amna Siddiqui; Shuja Abdul Karim Khan; Arouba Zafar (ziauddin University, 2024)
Background: Cervical cancer remains the third most common cancer among women in Pakistan. Human Papilloma Virus is a major cause of cervical cancer. This study aimed to access knowledge regarding cervical cancer, awareness about the vaccine against Human Papilloma Virus (HPV), to compare the differences in the attitude of different groups of women and factors that may help to improve acceptance of the vaccine. Methods: A cross-sectional study was carried out among 491 female students of Karachi. Participants were selected on random in the age group of 18 to 30; from different universities with the majority of the sample being medical students. Pearson Chi-squares and Mann Whitney U tests were applied for the key statistical analysis and p-value ≤0.05 was considered significant.   Results: In total of 343(69.9%) females were aware of the availability of the Human Papilloma Virus vaccine. Whereas, 60(19.3%) of the females were vaccinated against Human Papilloma Virus while, 239(77.1%) of the females said that they intend to get vaccinated against the virus in the future. A significant relationship was found between the recommendation of HPV vaccine and the intention to get the vaccination (p = 0.002). Awareness of the HPV vaccine was more common among medical university students (p <0.05).  Conclusion: A large proportion of female undergraduate students have limited knowledge about HPV as a cause of cervical cancer and the HPV vaccine as the way to protect against it. Similarly, very few of the subjects are reported to be vaccinated against virus.  Keywords: HPV Vaccines; Human Papilloma Virus; Cervical Cancer.